Guidelines for the Preparation of Feasibility Reports for Power Projects - Planning Commission (Planning Commission, 1992)
All Central public sector projects above a specified cost level require approval by the PIB prior to consideration by the Cabinet. Projects in all sectors (except Railways, Atomic Energy , Space, Non Conventional Energy, Science and Technology and Electronics) have to be considered by the Public Investment Board (PIB). (In the case of Scientific Departments such as Electronics, Science and Technology, the PIB is headed by the respective Secretaries).
Project Appraisal Division Planning Commission
Project Appraisal Division Planning Commission